PENGUJIAN ADAPTASI BEBERAPA VARIETAS JAGUNG HIBRIDA SPESIFIK LOKASI DI KABUPATEN MAJALENGKA - Yati Haryati; Anna Sinaga (Universitas Teuku Umar, 2018)
Some high yielding varieties of corn that has been released has wide adaptability, but the specific agro-ecological conditions are still required testing to see the response of plants to the specific agroecological conditions. Assessment conducted Farming Group Sawah Datar, Talaga Kulon Village, Sub District Talaga, District Majalengka the Month fromJune to September, 2014.Implementation of activities involving farmers as implementing activities. Treatment with implementing the technology components Integrated Crop Management (ICM) and non ICM. Objective assessment to determine the adaptation of several new varieties of hybrid maize in the local area conditions (location specific) by applying the Integrated Crop Management technology components that can improve theproductivity of maize.Observed data are agronomic data (plant height, number of leaves, stem diameter at the age of 30, 60 and 90 days after planting, flowering time of 50%, the number of cobs per plant, ear length (cm), diameter of cob, grain weight per ear (g) , 100 grain weight (g), cob weight (g), dry seed weight (t ha-1), weight stover (t ha), corn cob weight (t ha-1)), farming and supporting data (characteristics region and precipitation during the assessment).The performance of agronomic data were analyzed using t-test using SPSS for Windows 20.0 and the data were analyzed using a corn farm financial analysis and feasibility analysis of farming (R/C). The study showed that the productivity of hybrid corn varieties Bima-18 by applying the technology component Integrated CropManagement highest maize (9.24 t ha-1) than the Bima-19 (6.17 t ha-1) and the Bima-20 (7.05 t ha-1) that is suitable to be developed in the region Majalengka. The results of the analysis of the implementation of the components of PTT corn farming in hybrid corn varieties Bima-18 gives the value of R/C of 3.01. Keywords: adaptation, corn, hybrid corn varieties, Integrated Crop Management